2005
DOI: 10.1128/jcm.43.8.3944-3955.2005
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Candidate Periodontal Pathogens and Beneficial Species by Quantitative 16S Clonal Analysis

Abstract: Most studies of the bacterial etiology of periodontitis have used either culture-based or targeted DNA approaches, and so it is likely that pathogens remain undiscovered. The purpose of this study was to use culture-independent, quantitative analysis of biofilms associated with chronic periodontitis and periodontal health to identify pathogens and beneficial species. Samples from subjects with periodontitis and controls were analyzed using ribosomal 16S cloning and sequencing. Several genera, many of them uncu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

37
447
3
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 437 publications
(495 citation statements)
references
References 40 publications
37
447
3
8
Order By: Relevance
“…There is growing evidence from molecular investigations, including the present study, that members of the genus Veillonella form a major component of the subgingival microbiome in periodontal health (1,13,14). This ability of Veillonella to saturate the subgingival niche could play an important role in preventing colonization by pathogens and deserves further investigation as an indicator of clinical health.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is growing evidence from molecular investigations, including the present study, that members of the genus Veillonella form a major component of the subgingival microbiome in periodontal health (1,13,14). This ability of Veillonella to saturate the subgingival niche could play an important role in preventing colonization by pathogens and deserves further investigation as an indicator of clinical health.…”
Section: Discussionmentioning
confidence: 99%
“…The subgingival microbiome is complex, with several uncultivated and as-yet-unrecognized members (13,17), and hence, cultivation-based approaches have not been able to comprehensively examine the effects of smoking cessation on this ecosystem. We have previously reported that smoking cessation alters subgingival microbial profiles, determined using a comprehensive, open-ended molecular approach (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dental plaque is a biofilm, consisting of a diversity of co-aggregated bacteria (Al Ahmad et al, 2007;Dige et al, 2007). The commensal bacteria of dental plaque microflora (early colonisation) are important for the preservation of oral health and avoidance of oral disease (Socranscy et al, 2002;Kumar et al, 2005). Ecological shifts of commensal dental microflora (colonisation of early colonisers by late colonisers) due to environmental perturbations, such as excessive sugar intake, plaque over accumulation, can lead from dental health to caries and periodontal diseases (Allaker and Douglas, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, culture-independent molecular methods targeting small-subunit rRNA sequences (16S rRNA) in combination with high-throughput DNA sequencing have emerged as a popular approach to profile microbial flora from diverse sites of the human body. By amplification and deep sequencing of 16S rRNA gene segments, this approach has provided an unprecedented view of human-associated microbial communities and has uncovered novel or previously unrecognized microbes associated with health and disease (16,(28)(29)(30)(31). The Human Microbiome Project (HMP) data set is currently the largest reference data set (143 individuals) for the subgingival microbiome (32).…”
mentioning
confidence: 99%